A Proposed High-k Dielectric Based Thin Film Transistor for Next Generation Backplane Display Technology - Singh A.K.; Dikshit A.K.; Dixit B.; Kharche V.V.; Kamal; Rana J.S.; Chakrabarti P.; Pandey A. (My University, 2025)
A Zinc oxide (ZnO)-based thin film transistor (TFT) has been proposed to be built using a high-k La xTa 1-xO y} as an insulator to enhance their effectuation for backplane display technology. The device has been scrutinized on Silvaco ATLAS™ 2D simulator to examine the switching performance of the device for possible application in display driver circuits. To improvise the working of the TFT for the targeted application the atomic compositions of La and Ta in La xTa 1-xO y} have been converted to attune the dielectric constant of the insulator. The study reveals that the high-k insulator-based ZnO TFT can be modified to obtain high on/off current ratio of the order of 108 to ensure the high-speed operation with low sub-threshold swing 0.49 V/dec which is desirable for low power applications. It has been demonstrated that high-k dielectric insulator-based ZnO TFT has great potential for the development of cost-effective large-area display systems. © 2019 IEEE.